Systematic Literature Review (SLR): The Influence of Probiotic Use on the Productivity and Growth Rates of Broiler Chickens - Asrul, Asrul; Helda, Helda; Lengkana, Dewi; Marzuki, M. (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
Public perception generally limits the understanding of probiotic functions in broiler chickens to solely replacing the role of antibiotics, overlooking their other potential benefits. Therefore, a comprehensive systematic literature review (SLR) is warranted to elucidate the multifaceted advantages of probiotic addition on the development and overall performance of broiler chickens. This SLR adhered to the PRISMA guidelines. A total of 84 articles from 35 Scopus-indexed journals were screened and included following the PRISMA stages. The selected articles were subsequently visualized using covidence. The findings revealed eight key benefits of probiotics in broiler chickens: 1) enhanced growth performance; 2) improved gut health; 3) enhanced immune performance; 4) improved metabolic status; 5) reduced stress levels; 6) improved meat, carcass, and bone quality; 7) antibiotic replacement; and 8) enhanced synergistic effects with other feed additives Systematic Literature Review (SLR): Pengaruh Penggunaan Probiotik Terhadap Produktivitas Dan Tingkat Pertumbuhan Ayam Broiler ABSTRAK: Masyarakat pada umumnya mengetahui bahwa fungsi probiotik hanya bisa menggantikan peran antibiotik di ayam broiler, namun tidak mengetahui manfaat lain dari probiotik. Oleh karena itu perlu ada kajian SLR yang mengupas secara komprehensif manfaat suplementasi probiotik terhadap pertumbuhan dan performansi ayam broiler. SLR yang dibuat berpadoman pada panduan prisma. Ada 84 artikel dari 35 jurnal terindkes scopus yang tersaring dalam tahapan prisma. Artikel yang tersaring kemudian divisualisasikan dengan covidence. Hasilnya ada 8 manfaat probiotik terhadap ayam broiler yaitu 1) meningkatkan performansi pertumbuhan 2) Memperbaiki kesehatan usus 3) meningkatkan performasi Imun 4) meningkatkan status metabolik 5) pengurangan tingkat stress 6) peningkatkan kualitas daging, karkas dan tulang 7) pengganti antibiotik dan terakhir 8) Meningkatkan efek sinergitas dengan zat adiktif lainnya.